ROLE OF VASCULAR EXTRACELLULAR SUPEROXIDE DISMUTASE IN HYPERTENSION - Lob, Heinrich E. (2011)
Prior studies indicate that superoxide (O(2)(•−)) is important in modulation of blood pressure, but have not specifically identified the cell types or organs involved. We created mice with loxP sites flanking the extracellular superoxide dismutase (SOD3) gene. These mice were crossed with mice expressing inducible Cre-recombinase driven by the smooth muscle myosin heavy chain promoter allowing tissue specific deletion of SOD3. Deletion of SOD3 increased vascular O(2)(•−) and reduced vascular NO levels as detected by ESR. Despite these changes in NO and O(2)(•−), we did not observe increases in vascular inflammation caused by angiotensin II. Moreover, deletion of vascular SOD3 did not augment hypertension in response to angiotensin II. In additional studies, we also deleted SOD3 from the circumventricular organs by intracerebroventricular injection of an adenovirus encoding Cre-recombinase. While this raised blood pressure and augmented the hypertension caused by angiotensin II, these responses were not further increased by vascular deletion of SOD3. These data suggests that the extracellular superoxide dismutase in vascular smooth muscle is not involved in the genesis of angiotensin II-induced hypertension and further emphasize the role of central SOD3 in modulation of blood pressure.